Conventional treatment after myocardial infarction in routine clinical practice results in regression of left common carotid intima‐media thickness. (17th November 2013) - Jogestrand, Tomas; Agewall, Stefan; Gustafsson, Thomas; Henareh, Loghman
Summary This study aimed to evaluate the effect of standard medical treatment on the progression of atherosclerosis after a myocardial infarction, in an ordinary clinical setting, by measuring the right and left common carotid intima‐media thickness (IMT). The first investigation took place 3–12 months after the index event; the second took place 3·3–8·2 years after the first. In both investigations, the right and left carotid arteries of 102 patients were examined with an ultrasound duplex scanner. Common carotid IMT and calculated cross‐sectional intima‐media area (cIMa) were measured on both sides. More than 90% of the patients were treated with aspirin, beta‐blockers and statins. In the first investigation, IMT and cIMa were significantly greater on the left side compared to the right (IMT: 0·83 ± 0·22 and 0·74 ± 0·18 mm, P<0·001; cIMa: 18·2 ± 5·2 and 16·3 ± 5·1 mm2, P<0·001). In the second investigation, IMT on the left side was significantly reduced compared to the first investigation (0·79 ± 0·22 and 0·83 ± 0·22 mm, P<0·05) with a corresponding tendency towards a decrease in cIMa on the same side. In our study, conventional medical treatment after a myocardial infarction in ordinary clinical routines resulted in regression of the common carotid IMT on the left side. The significant side difference in IMT emphasizes the importance of where and how the carotid IMT is measured in studies using this surrogate end point.